Limited Effect of Biodiversity on the Multifunctionality of a Revegetated Riparian Ecosystem - Yueliang Jiang; Chen Ye; Manuel Delgado-Baquerizo; Guiyao Zhou; Yu Gong; Quanfa Zhang (Microorganisms)
Vegetation and microbial diversity play an essential role in ecosystem function. Active ecosystem restoration costs millions of dollars to increase biodiversity, yet when and how this restoration is effective when aiming at restoring multiple ecosystem functions (EMF) is still under debate. Here, we investigated the influence of a decade of restoration practices (i.e., active revegetation vs. natural rewilding) on the recovery of the ecosystem multifunctionality (EMF) provided by a riparian ecosystem. The experiment was conducted within the region of China’s Three Gorges Dam, and the area was subjected to a gradient of flooding disturbance. We found that active revegetation increased the plant diversity by 13~57% and EMF by ~2.6 times at the extreme flooding zone (~286 flooding days/year) of the riparian ecosystem, when compared with natural rewilding. Moreover, the positive relationship between plant diversity and EMF was weak, and abiotic factors (soil aggregate, pH, soil water content, and heavy metal content) were the dominant predictors for EMF, explaining 52% of the EMF variation. Revegetation impacted EMF both directly and indirectly via altering the soil properties. In addition, we also observed important trade-offs between plant biomass and soil functions (carbon storage and fertility). This study provides critical insights into whether and how a decade of active restoration is effective to recover the EMF supported by riparian ecosystems, and it highlights the importance of active revegetation in conservation and management programs for riparian ecosystems under future extreme flooding conditions.